Using NVDRS data for suicide prevention: promising practices in seven states. (14th December 2006) - Powell, V; Barber, C W; Hedegaard, H; Hempstead, K; Hull-Jilly, D; Shen, X; Thorpe, G E; Weis, M A
Abstract : Objectives: This article describes how seven states participating in a new public health surveillance system for violent death in the US, the National Violent Death Reporting System (NVDRS), have used data to support local suicide prevention activities. Setting: The NVDRS is unique in that it augments death certificate data with event and circumstance information from death investigation reports filed by coroners, medical examiners, and law enforcement. These data illuminate why the victim ended his or her life, fatal injury patterns, and toxicological findings at death. Results: Current suicide prevention efforts using these data fall into three categories: describing the problem of suicide and identifying opportunities for intervention; collaborating on statewide suicide prevention plans; and forming new partnerships for targeted prevention initiatives. Taken together, these three areas show early promise for state suicide prevention efforts. Conclusions: In each of the states, NVDRS data analyses are being shared with injury prevention colleagues, suicide prevention planning groups and policymakers, and adapted to respond to unique state and local suicide problems. A powerful surveillance tool, the NVDRS is bringing new clarity and direction to these state-based efforts. The NVDRS can serve as a model for other countries looking to establish timely suicide surveillance systems and data driven prevention strategies.